MAKNA SIMBOL SURYA MAJAPAHIT - Adisukma, Wisnu -; Yustana, Prima -; Kusmadi, Kusmadi -; Supriyanto, Ari - (Institut Seni Indoensia Surakarta, 2022)
The historical development in the frame of Nusantara cultural art will not be separated from the role of the great empire that once triumphed in Indonesia. Majapahit as one of the great kingdoms that in history was able to unite the archipelago certainly had a hand in the development of nusantara cultural arts, for example is the Majapahit ornament. One of the ornaments that is considered monumental is the Majapahit solar, because most consider it as the symbol of the Majapahit State, some consider it a symbol of reminding life. Learning and living the form and meaning of ornaments, it requires a certain knowledge and skill and a long time, considering that ornaments have various aspects such as: types of motifs, patterns, representations, values or meanings behind the form, depiction techniques, and different applications. Surya Majapahit also has unique and diverse characteristics of each very complex visual presentation ranging from the shape of the image, the naming of the parts of the image, and its meaning. And one of the important elements is the learning of the meaning behind a form that is acceptable and correctly understood, that the presence of ornaments in every building, especially sacred buildings, certainly has words and teachings that are used as guidelines for the supporting community in its time.